Iterative Algorithms for the Split Problem and Its Convergence Analysis. (27th May 2014) - Yao, Zhangsong; Rafiq, Arif; Kang, Shin Min; Zhu, Li-Jun
Abstract : Now, it is known that the split common fixed point problem is a generalization of the split feasibility problem and of the convex feasibility problem. In this paper, the split common fixed point problem associated with the pseudocontractions is studied. An iterative algorithm has been presented for solving the split common fixed point problem. Strong convergence result is obtained.